Sufi Culture of District Muzaffargarh; a Case Study on the Historicity and Festivity - Iqbal, Gulshan; Ahmad Khan, Dr. Mumtaz (Al-Amīr Research Journal for Islamic Studies, 2024)
The major concentration of present article is explicitly to reconnoiter that by what means Sufis executed their constructive walk-on part and toiled to foster the humanity through their instruction. The present paper specifically concentrates on socio-economic benefactions of Dervish and Saints in the fraternity of Muzaffargarh District. The Saints and dervish executed a significant laconic part in the social fabrication of the recent developed society as emblematic of the Islam. A large number of magnificent dervish and saints cropped up in mentioned locality and had not merely carried out a sumptuous chore of sermonizing Islam but also toiled for the betterment of the humankind through their collective spiritual favor to the population. Subsequent to the dawn of Islam, they demonstrated the role of pioneer of Islam meanwhile the epoch of gloom. They had slogged for the affluence of the human beings and eradicated entire types of breach and gulfs among the human beings. Altruism was a rudimentary chore of their preaching and they created cultural and mutual cooperation and understanding among the people. Mortals became best familiar of one and all beyond any bias and prejudice. District Muzaffargarh is the jam-packed and alluring hereabout and fecund land between the two rivers. Mortals acquired the gist of humanity and peace and through these saints Islam unfurl promptly. The noble Sufis are commendable for this disposition. The present artefact pinnacles the socio-religious ministrations of Dervish in Muzaffargarh. Keywords: Islam, Dervish, Sufi, Altruism, Society, Muzaffargarh